Tradisi Bhoka: Mahar Pernikahan di Kerajaan Muna - Astum, Habi Astum; Adnani, Soraya (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Marriage in Muna society is generally based on customs and religious teachings. The implementation of bhoka in traditional Muna marriages was first established by King Sugi Manuru in the 16th century, before the arrival of Islam in Muna. The uniqueness of the bhoka custom lies in its function, initially as a tax imposed by the government.. However, after Islam entered, there began to be a change where bhoka was transferred to function as a dowry for Muslim communities in the Muna Kingdom. The determination of bhoka cannot be separated from the social strata in the Muna Kingdom as the amount of bhoka is determined based on social class.  The method used in this research is the historical method involving heuristic, verification, interpretation, and historiography. The research findings indicate that the establishment of the bhoka custom from 1905 to 1960 AD arose due to the lack of concrete regulations regarding the amount of bhoka in marriages. Bhoka in traditional Muna marriages is essential for conducting wedding ceremonies as it serves as a dowry. Determining the amount of bhoka based on social strata in Muna is considered socially acceptable, given that the society in the Muna Kingdom is divided into several groups based on tasks and skills.